Ductal adenocarcinoma of the prostate: Clinical and biological profiles. Issue 12 (12th July 2017) - Vinceneux, Armelle; Bruyère, Franck; Haillot, Olivier; Charles, Thomas; de la Taille, Alexandre; Salomon, Laurent; Allory, Yves; Ouzaid, Idir; Choudat, Laurence; Rouprêt, Morgan; Comperat, Eva; Houede, Nadine; et al.
Abstract : Background: Ductal adenocarcinoma (DAC) is a rare and aggressive subtype of prostate cancer (PCa). In the present study, we analyzed the clinical and biological characteristics of DAC, in comparison with high grade conventional acinar PCa. Methods: Samples and data were retrospectively collected from seven institutions and centrally reviewed. Immunohistochemistry was performed on tissue microarrays to assess the expression of candidate proteins, based on the molecular classification of PCa, including ERG, PTEN, and SPINK1. SPOP mutations were investigated from tumor DNA by Sanger sequencing. Relationships with outcome were analyzed using log‐rank analysis and multivariable Cox regression. Results: Among 56 reviewed prostatectomy specimens, 45 cases of DAC were finally confirmed. The pathological stage was pT3 in more than 66% of cases. ERG was expressed in 42% of DAC, SPINK1 in 9% (all ERG‐negative), and two cases (ERG‐negative) harbored a SPOP mutation. Compared to high grade conventional PCa matched for the pathological stage, cell proliferation was higher ( P  = 0.04) in DAC, and complete PTEN loss more frequent ( P  = 0.023). In multivariate analysis, SPINK1 overexpression ( P  = 0.017) and loss of PSA immunostaining ( P  = 0.02) were significantly associated with biochemical recurrence. Conclusion: these results suggest that, despite biological differences that highlighted DAC aggressiveness, the molecular classification recently proposed in conventional PCa could also be applied in DAC.